Correlation between sustainability and smartness indicators in Brazilian cities: insights from the 5SenSu model - Pierucci, Pedro; Agostinho, Feni; Almeida, Cecília M. V. B.; Demétrio, Fernando J. C.; Giannetti, Biagio F. (Frontiers in Sustainable Cities, 2024)
To face the growing challenges of urbanization, urban management models grounded in the principles of sustainability and smart cities are being proposed. Despite their acknowledged importance, these models are often misunderstood or improperly applied due to a lack of thorough conceptualization, and they are frequently viewed as interchangeable. The aim of this study is to verify whether a correlation exists between indicators of sustainability and smartness in cities. For a sample of 130 Brazilian cities, their Sustainability Synthetic Indicator of System (SSIS) was computed using the Five-Sector Sustainability Model (5SenSu) and data sourced from the ‘Mandala ODS’ framework. Data concerning smart city were directly sourced from the ‘Connected Smart Cities’ framework. Results show that the 5SenSu model emerges as an alternative multicriteria method, epistemologically grounded in a conceptual model capable of quantifying the sustainability of cities. This approach enables quantitative diagnostics, rankings, and benchmarks, providing information to support decision-making processes. Moreover, the correlation analyses employed reveal a moderate linear correlation (Pearson coefficient of −0.61) and a moderate rank-order correlation (Spearman coefficient of −0.59) between sustainability and smartness. Hence, it would be premature to assume that a city deemed smart would automatically be sustainable, or vice versa. Acknowledging the existing limitations, this study contributes to discussions on the conceptual understanding and quantification through indicators of sustainable and smart cities, providing information for shaping effective public policies aimed at fostering more sustainable urban environments.